Eksperimen Pembelajaran Matematika melalui Strategi Problem Based Learning dan Inquiry Based Learning Berbasis Contextual Problem terhadap Hasil Belajar Ditinjau dari Kemampuan Penalaran Matematis Siswa Kelas VII - Nurlaili, Miftah Zuhri, Prof.Dr.Budi Murtiyasa, M.Kom (2017)
The aim of research are to describe and analyze: (1) the effect of mathematics learning with strategy Problem Based Learning and Inquiry Based Learning based Contextual Problem for learning outcomes, (2) the effect of mathematical reasoning abilities for learning outcomes, and (3) the interaction between the learning strategy and mathematical reasoning abilities for learning outcomes. Research conducted a experimental research with quasi-experimental design. The population used in this research were students of class VII SMP Negeri 23 Surakarta academic year 2016/2017. The sampling technique used is Cluster Random Sampling with methods used to collect data were documentation, test, and interview. The data analysis technique use is two-way analysis of variance with cell is not the same with a significance level of 5%. The results of data analysis was obtained: (1) there is effect of mathematics learning with strategy Problem Based Learning and Inquiry Based Learning based Contextual Problem for learning outcomes with Fa = 8.1049, (2) there is effect of mathematical reasoning abilities for learning outcomes with Fb = 159.2427, and (3) there is no interaction between the learning strategy and mathematical reasoning abilities for learning outcomes with Fab = 0.1435.